PENGARUH PELATIHAN KERJA, SOFT SKILL DAN MOTIVASI TERHADAP KINERJA KARYAWAN RESORT PT. DAMARLANGIT BIRU CISARUA BOGOR - Noviar, Rudy; Zuswana, Aries (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of job training, soft skills, and motivation on employee performance Resort at PT. Damarlangit Biru Cisarua Bogor. The method used zxxsis a quantitative approach with multiple linear regression analysis techniques using the help of SPSS software. With a sample of 133 employees. The results of the study showed that simultaneously (Test F), the variables of job training, soft skills, and motivation had a significant effect on employee performance, as shown by the Fcal value of 220,640 > Ftable 2,670 with a significance of 0.000. The value of the determination coefficient (Adjusted R Square) of 0.837 indicates that 83.7% of the variation in employee performance can be explained by all three independent variables. Partially (t-test), job training and motivation have a positive and significant influence on employee performance, and soft skills have a positive and significant effect. The soft skill variable has a tcal value of 3,300 > ttable 1.97796 and a significance of 0.001 < 0.05, so it has a positive and significant effect on employee performance. The job training variable became the dominant variable of 0.723.